Investigation of the Effect of Reaction Time, Weight Ratio, and Type of Catalyst on the Yield of Multi-Wall Carbon Nanotubes via Chemical Vapor Deposition of Acetylene - Dündar Tekkaya, Ezgi; Karatepe, Nilgün (Informa UK Limited, 2015)
The synthesis of multi-wall carbon nanotubes (MWCNTs) was studied using catalytic chemical vapor deposition of acetylene at 500°C for 30 and 60 min. Catalysts were prepared by impregnating Fe, Co, Ni, V, and bimetallic mixture of Fe-Co on MgO with a weight ratio of 1:100, 5:100, and 10:100. The effects of the reaction time, the type, and the weight ratio of the catalysts on the carbon yield of MWCNTs were investigated. Experimental results showed that the 10:100 weight ratio of Fe-Co:MgO had the highest carbon yield (81.97%) and the MWCNT to amorphous carbon ratio (100.6), whereas 10:100 V:MgO had the lowest carbon yield (8.44%). Statistical analyses indicated that increasing weight ratio enhanced the carbon efficiencies of Fe, Co, Fe-Co, and Ni catalyst; moreover, increasing the reaction time had a positive effect on the carbon efficiencies of Fe and V catalysts.
Keywords: QD001-65 General